2016
DOI: 10.3390/jcm5040039
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin—A Master Regulator of Epithelial-Mesenchymal Transition

Abstract: Osteopontin (OPN) plays an important functional role in both physiologic and pathologic states. OPN is implicated in the progression of fibrosis, cancer, and metastatic disease in several organ systems. The epithelial-mesenchymal transition (EMT), first described in embryology, is increasingly being recognized as a significant contributor to fibrotic phenotypes and tumor progression. Several well-established transcription factors regulate EMT and are conserved across tissue types and organ systems, including T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 118 publications
3
90
1
3
Order By: Relevance
“…5C, left panel). Surprisingly, two other targets of β-catenin, osteopontin [OPN; which is known as a master regulator of EMT (41) via its ability to stabilize vimentin (42)] and Axin2 [AXIN2, which enhances EMT via induction of Snail (43)] were not suppressed, and instead were increased in Daple-YE cells (Fig. 5C, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…5C, left panel). Surprisingly, two other targets of β-catenin, osteopontin [OPN; which is known as a master regulator of EMT (41) via its ability to stabilize vimentin (42)] and Axin2 [AXIN2, which enhances EMT via induction of Snail (43)] were not suppressed, and instead were increased in Daple-YE cells (Fig. 5C, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…OPN is a secreted non-collagenous, matrix glycoprotein, implicated in the progression of fibrosis and cancer and an influential factor in the tumor microenvironment (35,36). In the liver, OPN has been shown to modulate regeneration, inflammation and fibrosis and more recently, to induce dedifferentiation of hepatocytes (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…We found that constitutive phosphoactivation of Daple by Akt [mimicked by SD mutation] supresses several key canonical Wnt responsive β -catenin/TCF/LEF target genes (MYC, CCND1 and SFRP1;Figure 6J), consistent with its observed growth suppressive properties. Surprisingly, two other targets of β -catenin, osteopontin [OPN; which is known as a master regulator of EMT(Kothari et al, 2016) via its ability to stabilize vimentin(Dong et al, 2016)] and Axin2 [AXIN2, which enhances EMT via induction of Snail(Yook et al, 2006)] were not suppressed, and instead were increased in Daple-SD cells(Figure 6K), also consistent with its promigratory phenotype. Constitutive inactivation of the Akt→pS1428-Daple axis [as mimicked by SA and RC mutants] was associated with enhanced transcription of β catenin/TCF/LEF target genes (MYC and CCND1;Figure 6J) and suppression of key inducers of EMT (AXIN2 and VIM;Figure 6K); all consistent with the pro-growth and poorly motile phenotype of these cells.…”
mentioning
confidence: 75%